The Application of the MOORA Method in the Decision Making System for the Selection of the Best Employees at CV. Lautan Mas - Dedi Candro Parulian Sinaga; Preddy Marpaung; Baringin Sianipar (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2021)
Employees are one of the important elements in the running of the activities of a company CV. Ocean Mas. Therefore, employees are always required to always provide the best quality service in their work to increase consumer confidence and maintain competitiveness between companies engaged in the same field. To motivate and determine the quality of service work from each employee, a method is needed to be applied in helping the company in the decision-making system to determine the best employees. Where the method applied in determining the best employees is the Multi-Objective Optimization method on the basis of Ratio Analysis Simple (MOORA). With the application of the MOORA method, it can produce good, effective, and professional decisions in accordance with the best value, which is ranked 1. So with the application of the MOORA method, it can assist the company in determining its best employees effectively and professionally every period.